2015
DOI: 10.1016/j.oceaneng.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different procedures for the optimisation of a combined Diesel engine and organic Rankine cycle system based on ship operational profile

Abstract: At a time of strong challenges in relation to economic and environmental performance, the potential of waste heat recovery for ships fuel consumption has proved a considerable potential. This paper presents the comparison of four different procedures for the optimisation of an organic Rankine cycle based on an increasing level of accounting of the ship operational profile and on the inclusion of engine control parameters to the optimisation procedure. Measured data from 2 years of operations of a chemical tank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 42 publications
(36 reference statements)
1
24
0
Order By: Relevance
“…Baldi et al, in two different works [19,20], proposed the use of optimization techniques for diesel engine-ORC waste heat recovery systems based on the analysis of typical ships operating profiles. The case studies use, as baseline engines, MaK 8M32C fourstroke diesel engines with a power output of 3840 kW and some auxiliary units of about 683 kW.…”
Section: Introductionmentioning
confidence: 99%
“…Baldi et al, in two different works [19,20], proposed the use of optimization techniques for diesel engine-ORC waste heat recovery systems based on the analysis of typical ships operating profiles. The case studies use, as baseline engines, MaK 8M32C fourstroke diesel engines with a power output of 3840 kW and some auxiliary units of about 683 kW.…”
Section: Introductionmentioning
confidence: 99%
“…-Increase propulsion line overall efficiency in off-design and transient conditions -Increase main engines' maximum efficiency -Increase propeller efficiency -Retrieve energy converting waste heat to mechanical energy -Decrease energy demand To estimate energy consumption and CO2 emissions reduction, we have to establish the potential to increase the overall efficiency of the powertrain and performance in off-design conditions and establish the operational profile. Figure 2 shows the operational profile encountered by a working class vessel and a Panamax product tanker (Baldi 2015). Load of the diesel engine is 50 % of the time between 80 % and 100 % of full load.…”
Section: Tank-to-wheelmentioning
confidence: 99%
“…operational profile encountered by a working class vessel (left) and of a Panamax product tanker (right) (taken fromBaldi, 2015).…”
mentioning
confidence: 99%
“…In these heat exchangers, the gas or vapor side was assumed to dominate the heat transfer processes resulting in a UA value variation governed by the gas or vapor mass flow rate. The UA value at any off-design point was assumed to vary according to the following function, which is commonly used for simulating off-design characteristics of heat exchangers in power cycles [16,18,19,35]:…”
Section: Off-design Modelsmentioning
confidence: 99%
“…Although this is a suitable approach for preliminary performance estimations, an off-design analysis must be carried out in order to fully evaluate and compare different WHR unit options by accounting for inherent variations in vessel operation. This point was highlighted by Baldi et al [16] who demonstrated the importance of accounting for variations in ship operation, when optimizing a marine machinery system. Larsen et al [17] studied the NO x emission and specific fuel oil consumption (SFOC) trade-off for a large marine diesel engine equipped with an ORC bottoming cycle unit while accounting for off-design operation.…”
Section: Introductionmentioning
confidence: 96%